POLITIK HUKUM PEMBATASAN HAK PREROGATIF PRESIDEN DALAM PEMBENTUKAN KEMENTERIAN BERDASARKAN UNDANG-UNDANG KEMENTERIAN NEGARA: Politics of Law of Limitation of The President's Prerogative in the Formation of Ministries Based on The State Ministry Law - Mario Agritama S W Madjid (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
The 1945 Constitution of the Republic of Indonesia mandates that it is necessary to have Ministers to assist the President in carrying out his executive duties. The logical consequence is that the President has the prerogative to determine the formation of the structure of Ministers in their cabinet. Historically, the President’s prerogative has problems such as the uncertainty of the number and type of Ministries which resulted in the cabinet being unable to run effectively and efficiently in carrying out the functions. The State Ministry Law exists to regulate how the formation, change, and dissolution of State Ministries, so that there are limits to the President’s power to determine the structure of Ministries in the cabinet in order to support the effectiveness of the running of government. This study intend to examine how the legal politics of the existence of restriction on the President’s prerogative in determining the structure of their cabinet based on The State Ministry Law. The type of research used in this study is normative juridical with the library research method. The data source used is secondary data which includes primary, secondary, and tertiary legal materials. The results of this study is describe that The State Ministry Law has a responsive character because of the process of forming The State Ministry Law occurs through a democratic political configuration. Regarding the legal politics, the limitation of President’s prerogative in forming Ministries is aimed at strengthening the mechanism of checks and balances and strengthening the presidential system. Keywords: Politics of Law, Prerogatives, President, Ministry UUD 1945 mengamanatkan bahwa perlunya keberadaan Menteri untuk membantu Presiden dalam melaksanakan fungsinya di ranah ekesekutif. Konsekuensi logis dari hal tersebut adalah adanya hak prerogatif dari presiden untuk menentukan pembentukan struktur kementerian dalam kabinetnya. Dalam praktiknya hak prerogatif Presiden tersebut menuai problem, seperti tidak menentunya jumlah dan jenis kementerian yang berakibat pada tidak dapatnya berjalan efektif dan efisien suatu kabinet dalam menjalankan fungsinya. UU Kementerian Negara hadir sebagai upaya untuk mengatur bagaimana pembentukan, pengubahan, dan pembubaran kementerian negara, sehingga terdapat batasan terhadap kekuasaan presiden untuk menentukan struktur kementerian dalam kabinet dalam rangka menunjang efektifitas jalannya pemerintahan. Penelitian ini bertujuan untuk mengkaji bagaimana politik hukum dari adanya pembatasan hak prerogatif Presiden dalam menentukan struktur kabinetnya berdasarkan UU Kementerian Negara. Jenis penelitian yang digunakan dalam penelitian ini, yaitu yuridis normatif dengan dengan menggunakan pendekatan konstitusional dan peraturan perundang-undangan. Hasil dari penelitian ini menguraikan bahwa UU No. 39 Tahun 2008 tentang Kementerian Negara memiliki karakter yang responsif karena proses pembentukan UU a quo terjadi melalui konfigurasi politik yang demokrasi. Terhadap politik hukum pembatasan hak prerogatif presiden dalam pembentukan kementerian adalah bertujuan untuk memperkuat mekanisme check and balances dan memperkuat sistem presidensial. Kata Kunci : Politik Hukum, Hak Prerogatif, Presiden, Kementerian